2003
DOI: 10.1007/s00147-003-0550-1
|View full text |Cite
|
Sign up to set email alerts
|

Induction of specific stress response increases resistance of rat liver allografts to cold ischemia and reperfusion injury

Abstract: Heme oxygenase-1 (HO-1) has been shown to increase cellular resistance against oxidative injury, but the functional significance of this is currently obscure. We investigated the protective role of HO-1, induced by tin-protoporphyrin IX (SnPP), in attenuating liver transplantation injury. Lewis rats were intraperitoneally treated with saline as control, 50 pmol/kg of SnPP, or 2 mg/kg of cycloheximide (CHX) before SnPP injection. Gene expression of HO-1 was induced after either treatment with SnPP-or CHX + SnPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…SnPP treatment has been shown to inhibit enzyme activity, resulting in an induction of protein expression in rat liver allografts. 26 Similar to our data, SnPP treatment has been shown to reduce HO-1 enzyme activity and expression in rat basophil leukemia cells. 27 Although our data demonstrate elevated plasma HO-1 levels in response to rosiglitazone treatment, the exact source of this HO-1 is yet unknown, and the differential expression and regulation of HO-1 requires further investigation.…”
Section: Discussionsupporting
confidence: 91%
“…SnPP treatment has been shown to inhibit enzyme activity, resulting in an induction of protein expression in rat liver allografts. 26 Similar to our data, SnPP treatment has been shown to reduce HO-1 enzyme activity and expression in rat basophil leukemia cells. 27 Although our data demonstrate elevated plasma HO-1 levels in response to rosiglitazone treatment, the exact source of this HO-1 is yet unknown, and the differential expression and regulation of HO-1 requires further investigation.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, HO-1 overexpression by pharmacological means or via genetic engineering has been shown to exert potent cytoprotective effects in hepatic IRI transplant models, where both proinflammatory and apoptotic responses remain profoundly diminished in HO-1-overexpressing liver transplants (9 -11). In contrast, the lack or inhibition of HO-1 which generally accelerates host inflammatory responses, as shown in HO-1-deficient mice (12) as well as in HO-1 deficiency reported in humans (13), has yielded contrasting evidence in the liver IRI (11,14).…”
mentioning
confidence: 99%
“…We have previously reported that prior induction of HO-1 gene expression with a concomitant increased activity by hemin in donor livers could be associated with partial cytoprotection against hepatic cold I/R injury. Interestingly, SnPP, a potent competitive inhibitor of HO enzyme activity, did not eliminate the effects of hemin but rather conferred more beneficial effects, as indicated by histology and animal survival [35]. Since SnPP reduced HO enzyme activity below the baseline level, it was unlikely that the end products of heme degradation, including bilirubin and carbon monoxide, could be directly linked to cytoprotection against hepatic I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…After centrifugation at 10,000 g for 15 min, the amount of bilirubin was determined according to a method described previously [39]. As a positive control we used 60 pmol/kg of ferri-protoporphyrin IX chloride (Hemin, Sigma Chemical, St. Louis, Mo., USA), a potent inducer of HO-1 activity [35]. Enzyme activity was expressed as picomoles of bilirubin per milligram of tissue protein generated for 30 min.…”
Section: Immunohistochemistrymentioning
confidence: 99%